Kinematic determinants of performance parameters during golf swing. (May 2019) - Khuyagbaatar, Batbayar; Purevsuren, Tserenchimed; Kim, Yoon Hyuk
In golf, the trunk and pelvis kinematic variables are often related to measures of performance due to the highly complex and multi-joint movements involved in swings. However, it is unclear how specific body segments or joints contributed to the golf performance parameters. Therefore, the purpose of this study was to identify the key joints, including those of the upper and lower trunk, that are associated with golf performance parameters, such as X-Factor and pelvis motion. A motion capture system was used to obtain three-dimensional kinematics of golf swings performed by 10 low handicap male golfers. Based on regression analysis, right knee adduction, right shoulder external rotation and left elbow extension in ball address to top of the backswing and left knee adduction and lower trunk right bending with left rotation in top of the backswing to end of follow-through were presented as predictor variables for the X-Factor. For pelvis movement, a greater number of joint angles were associated with pelvis posterior tilt during backswing and pelvis motion to target with right rotation during downswing/follow-through. This study provides fundamental details of the movement mechanisms of major joints, as well as their relationships with performance parameters. Such understanding can be combined with training to improve the golfing skill and prevent possible injuries.